Exploration of Sociology Education Students' Multicultural Awareness of Social and Cultural Diversity - Jalal; Suraiya Chapakiya; Nurul Adillah Ramlan (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2026)
This study explores the multicultural awareness of Sociology Education students toward social and cultural diversity in higher education contexts. Multicultural awareness has become an important issue in the digital and globalization era due to increasing social interaction, cultural exchange, and challenges related to intolerance, stereotypes, and social polarization. Sociology Education students play a strategic role as prospective educators and social agents who are expected to promote inclusive and democratic values in society. Therefore, understanding how students perceive and experience multiculturalism is essential in strengthening social harmony in multicultural academic environments. This study employed a qualitative phenomenological approach to explore students’ lived experiences regarding diversity and intercultural interaction. The research was conducted from March to May 2026 at the Sociology Education Study Program of Universitas Megarezky involving seven participants selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and analyzed using Jürgen Habermas’s communicative action theory. The findings revealed that students generally demonstrated positive multicultural awareness reflected in tolerance, respect for differences, empathy, and openness toward intercultural communication. Interaction with peers from different cultural backgrounds contributed to the development of inclusive attitudes and social understanding. However, challenges such as stereotypes, communication misunderstandings, and the negative influence of social media were still identified. The study concludes that communicative interaction and multicultural learning significantly contribute to the development of students’ multicultural awareness. This research provides insights for higher education institutions in strengthening multicultural education and inclusive academic environments.